Sensitivity linearization technique for a time based MEMS accelerometer - Dias, R. A. (2011)
A high-resolution, high-sensitivity capacitive accelerometer based on pull-in time measurement is described in this paper. The high sensitivity of pull-in time is being explored to implement high performance accelerometers, and non-linearity is the main characteristic compromising device performance. An electrostatic compensation technique that addresses the non-linearity problem, based on pull-in time duration control, is presented and tested. Capacitive parallel-plates MEMS structures were used and the measured sensitivities for different acceleration ranges confirm the potential of this technique and the overall accelerometer concept. The results show an accelerometer with 0.26 μs/μg sensitivity, over a 120 dB dynamic range.